2022
DOI: 10.1093/bjd/ljac097
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diagnostic criteria for atopic dermatitis and proposal of novel diagnostic criteria for adult and elderly Chinese populations: a multicentre, prospective, clinical setting-based study

Abstract: Background A previous validation study showed a very low sensitivity and higher specificity associated with Hanifin and Rajka criteria (H&R) and the UK Working Party criteria (UKWP) in diagnosing AD vs. the Chinese criteria of atopic dermatitis (AD) for children (CCAD). However, their diagnostic efficacy in adult and elderly Chinese populations remains unknown. Objectives To validate the diagnostic efficacy of three sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…14 Some studies have explored the diagnosis of elderly AD. Chello et al 22 suggested a set of clinical and serological criteria that might be able to guide the diagnosis of AD in elderly Caucasian; Yue et al 23 applied the “Chinese criteria of AD for children” to assess the diagnostic sensitivity and specificity for adult and elderly AD, and found that its sensitivity was significantly higher than the H.R. criteria and UKWP criteria, while the specificity decreased.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some studies have explored the diagnosis of elderly AD. Chello et al 22 suggested a set of clinical and serological criteria that might be able to guide the diagnosis of AD in elderly Caucasian; Yue et al 23 applied the “Chinese criteria of AD for children” to assess the diagnostic sensitivity and specificity for adult and elderly AD, and found that its sensitivity was significantly higher than the H.R. criteria and UKWP criteria, while the specificity decreased.…”
Section: Discussionmentioning
confidence: 99%
“…57 participants (AD, n=38; healthy control, HC, n=19)were recruited from the Dermatology Department of the Second Affiliated Hospital of Harbin Medical University, Harbin, China. The Chinese criteria ( 20 , 21 ) was used to diagnose AD participants, and the Eczema Area and Severity Index (EASI) criteria was used to assess the degree of clinical symptoms. Healthy subjects were defined by a lack of history of visible signs of skin damage that is indicative of AD.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Chinese criteria for adult and adolescent AD point to the mandatory presence of persistent or recurrent symmetrical eczema for more than 6 months. In addition, one or more of the following elements are necessary for the diagnosis: personal and/or family history of atopic diseases; elevated total serum IgE levels and/or positive allergen-specific IgE and/or eosinophilia ( 23 , 24 ) . Japanese criteria consider AD as a chronic disease characterized by fluctuating phases of remitting and relapsing eczema with pruritus as a primary symptom.…”
Section: Atopic Dermatitis Diagnosismentioning
confidence: 99%